Pengelolaan Asset Daerah Dengan Minimalisasi “Expected Opportunity Loss” - Dewi Andini Widyastuti; Basukianto Basukianto (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Good asset management will contribute greatly to local governments in improving public services. On the other hand, if the management is bad, it will also have a bad impact on the local government. The purpose of this study is to determine the amount of potential lost from assets, constraints in asset management and how to minimize expected opportunity loss in regional asset management. This type of research is a qualitative research with an exploratory level. This means that this study aims to explore broadly about the causes or things that cause something to happen and we don't know yet. The object of this research is the expected opportunity loss in the management of regional assets of the Regional Secretary of Central Java Province. The results showed that EOL in the management of regional assets by the Regional Secretary of Central Java Province through BPKAD fluctuated. EOL in asset management is as follows: 4% in 2019, 30% in 2020 and 17% in 2021 of all potential asset revenues of the Central Java Provincial Government. The EOL level is quite high compared to the target number and total assets owned by the Central Java Provincial Government, resulting in the emergence of expected opportunity loss in terms of regional asset management. The expected opportunity loss condition is due to the low level of absorption of realization of regional asset management income, resulting in arrears from the tenants and due to the impact of covid, some tenants can only pay in 2022.